2013
DOI: 10.1002/oby.20530
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional associations of objectively measured physical activity, cardiorespiratory fitness and anthropometry in European adults

Abstract: Objective: To quantify the independent associations between objectively measured physical activity (PA), cardiorespiratory fitness (CRF), and anthropometry in European men and women. Methods: 2,056 volunteers from 12 centers across Europe were fitted with a heart rate and movement sensor at 2 visits 4 months apart for a total of 8 days. CRF (ml/kg/min) was estimated from an 8 minute ramped step test. A cross-sectional analysis of the independent associations between objectively measured PA (m/s 2 /d), moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…This finding is also in agreement with previous evi dence that SED is positively associated with waist circum ference independent of MVPA (10). A further study of 2056 European healthy middle-age adults found a positive as sociation between SED measured using accelerometry and anthropometric measures including waist circumference (32), and Smith et al (22) found a significant positive as sociation between SED and VAT in women. Other studies did not find such associations, but these are characterized by smaller study samples and/or self-reported PA assess ment (15,20).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This finding is also in agreement with previous evi dence that SED is positively associated with waist circum ference independent of MVPA (10). A further study of 2056 European healthy middle-age adults found a positive as sociation between SED measured using accelerometry and anthropometric measures including waist circumference (32), and Smith et al (22) found a significant positive as sociation between SED and VAT in women. Other studies did not find such associations, but these are characterized by smaller study samples and/or self-reported PA assess ment (15,20).…”
Section: Discussionsupporting
confidence: 90%
“…A recent large study of objectively measured PA and an thropometry has suggested that there may be sex differences in such associations (32). One would perhaps expect sex differences in the association between PA and abdominal fat distribution, given the well-known difference in abdominal fat distribution between the sexes, although we had no spe cific a priori hypothesis regarding this.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…These results are in line with the results of a cohort study on 184,697 Austrian adults (85,000 men, 99,697 women), which showed higher percentages of women in comparison to men in the BMI-classes below 22.4 (42.4% vs. 21.3%, respectively) [18]. Other studies, conducted on German and European populations, confirm a higher mean BMI of adult men compared to women (Germans: 26.1 vs. 25.2; Europeans: 27.1 vs. 25.3) [19,20]. In comparison to mountain hikers in general [3], the victims in the present study had a slightly higher mean BMI.…”
Section: Discussionmentioning
confidence: 80%
“…A common viewpoint is that health and performance levels could best be improved by activities starting from moderate to vigorous levels (Wientzek et al, 2014). According to the recommendation of the American College of Sports Medicine (ACSM), if moderate to vigorous intensities are targeted, the maximum heart rate (HRmax) during exercise should be from 64% to 94% for healthy adults.…”
Section: Introductionmentioning
confidence: 99%